Kenapa Muzakki Percaya Kepada Lembaga Amil Zakat? - Halimah Assa’diyah; Sigit Pramono (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2019)
The study aimed to examine the influence of accountability, transparency of the Zakat Organization towardz Muzakki's Trust. The respondents are the muzakki who registered in the Central BAZNAS and Baitul Maal Hidayatullah LAZ. Baitul Maal LAZ and Central BAZNAS was taken by using non-purposive sampling. Data were collected by the questionnaire. The data are analyzed by the Structural Equation Modeling (SEM) with the PLS approach. The study indicated that accountability do not has any significant affect towards the muzakki's trust otherwise the transparency has a significant effect towards the muzakki's trust